Addition of lithiated enol ethers to nitrones and subsequent Lewis acid induced cyclizations to enantiopure 3,6-dihydro-2H-pyrans – an approach to carbohydrate mimetics - Pfrengle, Fabian (Beilstein-Institut, 2010)
A stereodivergent synthesis of enantiopure 3,6-dihydro-2H-pyrans is presented. The addition of lithiated enol ethers to carbohydrate-derived nitrones afforded syn- or anti-configured hydroxylamine derivatives 4a–d that were cyclized under Lewis acidic conditions to yield functionalized dihydropyrans cis- or trans-5a–d containing an enol ether moiety. This functional group was employed for a variety of subsequent reactions such as dihydroxylation or bromination. Bicyclic enol ether 19 was oxidatively cleaved to provide the highly functionalized ten-membered ring lactone 20. The synthesized enantiopure aminopyrans 24, 26, 28 and 30 can be regarded as carbohydrate mimetics. Trimeric versions of 24 and 28 were constructed via their attachment to a tricarboxylic acid core.